Asia inside out : changing times - Tagliacozzo, Eric; Siu, Helen F.; Perdue, Peter C., 1949- (Harvard University Press, 2015)
The first of three volumes surveying the historical, spatial, and human dimensions of inter-Asian connections, Asia Inside Out: Changing Times brings into focus the dynamic networks that have linked peoples from Japan to Yemen over the past five centuries. Each author examines a single year or decade that redefined Asia.